Expression of BCL-2 and bax genes induced by an ovarian extract of Singkarak Lake Pufferfish (Tetraodon leiurus) in breast cancer cell - Hanif, Monica Mulnia; Tjong, Djong Hon; Syaifullah,; Santoso, Putra; Efrizal,; Roesma, Dewi Imelda (Penerbit Universiti Kebangsaan Malaysia, 2022)
It is known that the ovarian extract of Singkarak Lake Pufferfish (Tetraodon leiurus) has the potential for chemoprevention in MCF-7 cells. However, the expression of Bcl-2 and Bax genes was associated with cancer. Therefore, this study aimed to analyze the Bcl-2 and Bax gene expression induced by the ovarian extract of Singkarak Lake Pufferfish (Tetraodon leiurus) in MCF-7. The method in this study was an in vitro experiment using MCF-7 control cells and MCF-7 cells induced by the ovarian extract of Singkarak Lake Pufferfish (Tetraodon leiurus), and Real-time PCR was used to examine the expression of Bcl-2 and Bax genes. The result showed that the expression of the Bcl-2 gene had an insignificant decrease (p>0.05) by 15%, and the expression of the Bax gene had a significant increase (p<0.05) by 489% compared to the control. These results support that ovarian extract Singkarak Lake Pufferfish (Tetraodon leiurus) can be alternative cancer chemoprevention.